PATHOMORPHOLOGICAL CHANGES IN NEWBORN MORTALITY IN ANDIJAN REGION - Mamatalieva, Mavlyuda (International Journal of Scientific Pediatrics, 2023)
Abstract: The mortality rate of newborn babies shows the socio-demographic development of the society, the social condition of the population, the activity of the health care system and the society’s attention to human life. Research purpose and materials: comparative study of the causes of death in the pathology of the respiratory system of newborns and pathomorphological changes in their internal organs, gender, number of births, and other somatic diseases with the development of death. In the research, the archival materials of the departments of pathomorphology and histology of the deaths of infants in the years 2012-2016 examined by the forensic medicine expertise of Andijan region and the bureau of pathological anatomy of Andijan region were studied. Results. Analytical studies showed that the distribution of neonatal deaths by age was more frequent in the 1st month (preterm neonatal death) and in the 4th month (postnatal death), parallel to the increase in age. postnatal mortality has been seen to decrease. Conclusion: Analytical studies of pathomorphological changes in infant mortality in Andijan region show that the incidence of neonatal mortality depends on age (neonatal mortality), and is observed more frequently in the 4th month (postnatal mortality). , parallel to increasing age, it was seen that postnatal deaths decrease. keywords: babies, death, pathomorphology.